2020
DOI: 10.3389/fonc.2020.585083
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Values of Preoperative Inflammatory and Nutritional Markers for Colorectal Cancer

Abstract: Background: Increasing evidence indicates that inflammation and nutritional status are associated with survival outcomes in patients with colorectal cancer (CRC). This study aimed to investigate the prognostic values of preoperative inflammatory and nutritional factors and develop a prognostic model individually predicting overall survival (OS) and disease-free survival (DFS) in patients with CRC. Methods: We retrospectively collected data on patients with CRC who underwent radical surgery. Independent prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…Tumor-associated neutrophils (TANs) can recruit immune T cells, which may promote tumor growth, progression, and resistance to chemotherapy [ 36 ]. Zhang et al [ 37 ] demonstrated that TANs can independently influence OS and DFS in colorectal cancer. Tregs reduce immunotherapy effectiveness due to their antitumor immune effects [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-associated neutrophils (TANs) can recruit immune T cells, which may promote tumor growth, progression, and resistance to chemotherapy [ 36 ]. Zhang et al [ 37 ] demonstrated that TANs can independently influence OS and DFS in colorectal cancer. Tregs reduce immunotherapy effectiveness due to their antitumor immune effects [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Daniel Boakye et al constructed a clinical nomogram incorporating comorbidities and functional status, which could substantially enhance prediction of CRC prognosis (37). Likewise, a novel nomogram i n c o r p o r a t i n g p r e o p e r a t i v e i n fl a m m a t o r y a n d nutritional markers, built by Zhang Nannan et al (5), could individually predict both OS and disease-free survival (DFS) of patients with CRC. Here, the aim of our study was to construct a convenient and clinically available prognostic model to better predict outcomes of CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…To calculate the LODDS value, negative LNs (nLNs) representing non-metastatic lymph nodes should be derived by subtracting pLNs from the harvested LNs. Afterwards, LODDS was determined as the following formula: LODDS = In ([pLNs + 0.5]/[nLNs + 0.5]) (5,15).…”
Section: Crc Patients and Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The calibration was calculated by the “calibrate” function with the parameter “cmethod = KM, method = boot, m = 80.” Discrimination was evaluated by Harrell’s concordance index (C-index) and ROC curve. A higher area under curve (AUC) value revealed superior model discriminative ability, and a higher C-index value demonstrated better model-fitting performance ( Zhang et al, 2020 ). Decision curve analysis (DCA) was further performed to measure and compare the clinical utilities of the different prognostic models.…”
Section: Methodsmentioning
confidence: 99%